Komunikasi Interpersonal Orangtua Pendamping Warga Negara Berkebutuhan Khusus Sebagai Pelaku UMKM : Studi Deskriptif Komunikasi Interpersonal Warga Negara Berkebutuhan Khusus Sebagai Pelaku UMKM di Pasar Gintung Ciputat Tangerang Selatan - Barizki, Rezzi; Marestiani, Rini (Prisani Cendekia Institute, 2024)
The role of parental communication with children can provide input and solutions and influence them. The communication techniques that WNBK parents convey to children who have a diagnosis of deafness are using sign language, visually impaired difficulty adapting to a new place through touching, mentally impaired using simple language or two words, autism repeated delivery, using body language and speaking full of emphasis and down syndrome limited vocabulary, hearing impairment using sign language, impaired speech less clear, impaired the delivery of the word subtly. The purpose of this study is to determine the interpersonal communication carried out by WNBK accompanying parents to children with special needs and find out the obstacles to interpersonal communication carried out by WNBK UMKM companion parents. The research methods used are qualitative. Data collection techniques in this study used interview, observation, and documentation techniques. Data analysis techniques consist of data collection, data reduction, data presentation, and decision-making. The data validity technique used consists of the persistence of observation and triangulation. The result of this study is interpersonal communication between parents and children with special needs to maintain an effective interpersonal communication process between parents and children, especially related to diverse values so that effective interpersonal communication will also be created for children and will affect the performance and success of a program and facilitate the achievement of goals. The child's openness to parents in communicating provides all information about all problems or obstacles to the child.